Sandal-an Exotic ? - Rajagopal Shetty, H. (Indian Forester, 1977)
India holds near monopoly in the world trade of sandalwood and its oil fetchs Rs. ten crores foreign exchange. It is one of the most studied species in Indian Forestry, and was held as indigenous to peninsular India. Yet in recent years doubts have been expressed about its origin. The record of growing stock available over the last sixty years for the sandal foreets of the Javadi Hills in Vellore Forest Division of Tamil Nadu throws some fresh light to show, that sandal is a new immigrant in the eco-system. Dutch East Indies of Indian archepilago was probably its home, though it has naturalised in India perbaps for centuries.